Thickening Transregionalism: Historical Formations of Science, Technology, and Medicine in Southeast Asia. Issue 4 (1st December 2018) - Anderson, Warwick
Abstract: This article offers an overview of science and technology studies (STS) in Southeast Asia, focusing particularly on historical formations of science, technology, and medicine in the region, loosely defined, though research using social science approaches comes within its scope. I ask whether we are fashioning an "autonomous" history of science in Southeast Asia—and whether this would be enough. Perhaps we need to explore further "Southeast Asia as method, " a thought style heralded here though remaining, I hope, productively ambiguous. This review contributes primarily to the development of postcolonial intellectual history in Southeast Asia and secondarily to our understanding of the globalization and embedding of science, technology, and medicine.